Police Innovation and Control of the Police
X, 223 p.
Keywords: Police Innovation and Control of the Police: Problems of Law, Order and Community brings together an impressive array of scholars and analysts to examine the impact of the development of crime control strategies on problems of police corruption and abuse. The text provides an historical overview of the development of legal control of the police, and examines the challenges that recent innovations, such as community or problem oriented policing present to the traditional, historical mechanisms for maintaining control of the police. Additionally, a comparative perspective is featured that draws upon the experiences of the Gorbachev era in the Soviet Union as well as on the history of European law enforcement over the last century. This book is instrumental for encouraging discussion and debate of police innovation and its impact on the ability of society to control the police abuse. In light of the Los Angeles riots of the Spring of 1992, scholars, practitioners, and students of crime prevention studies, criminology, and psychology will find this volume timely, topical, and provocative.